Application of Animal Waste Fertilizer (KOHE) Toward Growth and Results of Carrot (Dautus carota.L) Plant in Cisondari Village Pasirjambu District, Jawa Barat - Indrawati, Etty (University of Brawijaya, 2020)
ABSTRACTCisondari village is one of the villages in West Java with producers of various types of vegetable crops, dairy farms and chicken farms. The largest dairy cattle population in the village of Cisondari is in the Pasirjambu sub-district, the impact of cattle farming is the waste of manure dung (kohe) which has the potential to produce methane gas (CH4) as one of the greenhouse gases (GHG). During this time the handling of cow dung is dumped directly into the river, so that it can pollute the river directly. This research is one of the activities in the Hibah Community Service Program in Cisondari village. This study used a simple Randomized Block Design (RBD) consisting of six (6) treatments with three (3) replications tested on carrot (Daucus carota) Organic fertilizer application which was used as treatment ie soil without fertilizer, soil mixed with chicken manure without fermentation, fermented chicken manure, chicken manure + Vermicompost (50: 50), compost, chicken manure + vermicompost (30: 70). To determine the effect of giving organic fertilizer on growth and yield of carrot (Daucus carota), the F test with a level of 5% was used, namely the Variety Analysis Test (ASR). The results of research on carrot show that, in general, the application of organic fertilizer can increase the yield of carrot. The highest yield of carrots is found in carrot which are fertilized by fermented chicken manure (P2); followed by carrot plants fertilized with chicken manure + Vermicompost (50:50) (P3); Chicken manure + Vermicompost (30:70) (P5); Non-fermented chicken manure (P1); Vermicompost (Po).Keywords: Animal manure, carrots, vermicompost, fermentation, organic fertilizer